2015
DOI: 10.1007/s00784-015-1590-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation comparing the fit of all-ceramic crowns obtained from silicone and digital intraoral impressions

Abstract: http://www.isrctn.com/ISRCTN16111844.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 25 publications
5
73
0
7
Order By: Relevance
“…The choice of impression type thus does not influence the precision of the zirconia crown's adaptation. This is in line with previously published results 891011…”
Section: Discussionsupporting
confidence: 94%
“…The choice of impression type thus does not influence the precision of the zirconia crown's adaptation. This is in line with previously published results 891011…”
Section: Discussionsupporting
confidence: 94%
“…Difference in parameters such as the considered cement space, which was 40 μ in our study and 50 μ in the study by Berrendero et al, can also explain the difference in the results. Some clinical studies reported greater marginal gap compared to our values, which may be attributed to the different types of restorations. According to Pak et al, addition of porcelain to coping caused distortion and decreased the fit of restorations.…”
Section: Discussionmentioning
confidence: 99%
“…The overall size of internal gap in our study agreed with that in many clinical studies . Our value was lower than that reported in some other studies, which may be due to the use of coating powder spray before scanning in some digital systems such as Lava C.O.S. The thickness of this layer, could affect the restoration fit .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All ceramic, CAD/CAM full coverage restorations are becoming increasingly popular as this method provides expedient prosthesis fabrication with acceptable marginal accuracy . Compared to traditional laboratory‐fabricated cast restorations, CAD/CAM‐generated restorations rely more on adhesive technology, which proponents claim can compensate for loss of traditionally recommended preparation features .…”
Section: Introductionmentioning
confidence: 99%